Comparison of Soil Moisture Obtained by SMOS L-Band Radiometer and in-situ Measurement using Gravimetric Method of Rajasthan Site - Calla, O PN; Kalla, Abhishek; Gadari, Kishan Lal; Sharma, Rahul; Agrahari, Sunil Kumar; Rathore, Gaurav (Annals of Arid Zone, 2016)
. Â